2018
DOI: 10.1111/jmwh.12896
|View full text |Cite
|
Sign up to set email alerts
|

Distance from Home Birth to Emergency Obstetric Services and Neonatal Outcomes: A Cohort Study

Abstract: Introduction Little is known about the relationship between distance from hospital services and the outcomes of planned home births. We examined whether greater driving distance from a hospital with continuous cesarean capability was associated with a higher risk of adverse neonatal outcome among individuals who were planning to give birth at home. Methods Using an intention‐to‐treat analysis, we conducted a population‐based cohort study of 11,869 individuals who planned to give birth at home in Ontario, Canad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…Evidence from travel time studies Description of included studies Fifteen studies explored the impact of travel time from a woman's home to an OU (see table 7). Two studies (one reported as an abstract only) were conducted in the UK, [29][30][31] three studies in France, [32][33][34] three studies (reported in five articles) in the Netherlands, [35][36][37][38][39] one study reported in two articles from Norway, 40 41 five studies in Canada [42][43][44][45][46] and one study in Japan. 47 Eleven studies were of a retrospective cohort design, one was a prospective cohort study, 39 one was a before-and-after design 47 and two were case-control studies.…”
Section: Hypoxic-ischaemic Encephalopathy (Hie)mentioning
confidence: 99%
See 4 more Smart Citations
“…Evidence from travel time studies Description of included studies Fifteen studies explored the impact of travel time from a woman's home to an OU (see table 7). Two studies (one reported as an abstract only) were conducted in the UK, [29][30][31] three studies in France, [32][33][34] three studies (reported in five articles) in the Netherlands, [35][36][37][38][39] one study reported in two articles from Norway, 40 41 five studies in Canada [42][43][44][45][46] and one study in Japan. 47 Eleven studies were of a retrospective cohort design, one was a prospective cohort study, 39 one was a before-and-after design 47 and two were case-control studies.…”
Section: Hypoxic-ischaemic Encephalopathy (Hie)mentioning
confidence: 99%
“…Only singleton births were included in five studies. 30-32 35-38 42 One study 39 specifically enrolled women with postnatal haemorrhage after home birth, and one study 42 focused on planned home birth regardless of the actual place of birth.…”
Section: Hypoxic-ischaemic Encephalopathy (Hie)mentioning
confidence: 99%
See 3 more Smart Citations